The influence of physical culture on the psychological state of a person ("Journal "U". Economy. Management. Finance.", 2023)
The article considers the influence of a person's physical activity on his psychological state. The article reflects the relationship between sports and the emotional stability of people. The analysis of factors influencing the psychological state of a person is also carried out.
Keywords: sport; human; physical activity; lifestyle